2016
DOI: 10.1038/srep33920
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent deletion in the SLC5A2 gene including the intron 7 branch site responsible for familial renal glucosuria

Abstract: Familial renal glycosuria (FRG) is caused by mutations in the SLC5A2 gene, which codes for Na+-glucose co-transporters 2 (SGLT2). The aim of this study was to analyze and identify the mutations in 16 patients from 8 families with FRG. All coding regions, including intron-exon boundaries, were analyzed using PCR followed by direct sequence analysis. Six mutations in SLC5A2 gene were identified, including five missense mutations (c.393G > C, p.K131N; c.1003A > G, p.S335G; c.1343A > G, p.Q448R; c.1420G > C, p.A47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In the current study, we found two splice site variants: IVS1-16C > A and c.1152-63del. However, the effect of these two splicesite variants has been verified in previous studies [13,22]. Therefore, we did not retest the effect of splice-site variants in cDNA in the current study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In the current study, we found two splice site variants: IVS1-16C > A and c.1152-63del. However, the effect of these two splicesite variants has been verified in previous studies [13,22]. Therefore, we did not retest the effect of splice-site variants in cDNA in the current study.…”
Section: Discussionmentioning
confidence: 77%
“…Renal biopsy is not obligatory for FRG patients; therefore, SLC5A2 cDNA from the kidney is almost impossible to obtain. Although there are a few reports about splice-site variants [4,5,22,23], the effect of splice-site variants is very difficult to verify in cDNA. We searched through NCBI GEO profiles and found that the SGLT2 protein can be expressed in peripheral white blood cells and lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…No further variant explaining the patient phenotype could be found in the whole-exome sequencing data. In order to test the functional significance of c.706-2A>C, we performed a minigene splicing assay with the pSPL3 vector [14] ( Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…The minigene splicing assay was performed as previously described [14]. PCR fragments of CYP26C1 intron3-exon4-intron4 genomic region were cloned into the splicing vector pSPL3 using specific primers linking the EcoRI and BamHI restriction enzyme sites (forward primer 5′-GTA-CAGGGAAAGGGCAATGG-3′; reverse primer 5′-GAGTTTGATCCTGAGCCCCT-3′).…”
Section: Minigene Splicing Assaymentioning
confidence: 99%
“…To investigate the effect of the splice site mutation located in intron 3 (c.526 + 1G>A), we designed a minigene including exon 3 and part of introns 2 and 3 of the EDA gene using the exon trapping pSPL3 plasmids (Invitrogen Corporation, Carlsbad, CA, USA; Zhao et al., ; Kimani et al., ). Fragments encoding the wild‐type or mutant alleles involving exon 3 (24 bp) and flanked by the upstream (144 bp) and downstream (141 bp) intronic sequences were cloned into the pSPL3 splicing vector using specific primers incorporating the 5′ Eco R I and 3′ Sac I restriction enzyme sites.…”
Section: Methodsmentioning
confidence: 99%